Pasta 00731 - volumes 01 e 02 end. quarteirões fechados da praça Sete de Setembro.: apenso ao processo n. - 01.059220.95.10 : sobre a produção de uma nova sensibilidade urbana pela arquitetura - Frederico Canuto (2005)
Considering that Architecture defines its specificity in a continuous movement of differentiation and appropriation of knowledge from other fields that convey to it, like urban planning, geography, history, ethnography, art and sociology, among others that somehowhave a critical relation with space and its production, this work seeks to establish, through interdisciplinary movements, new ways of thinking and acting upon the relations of production of an amplified dimension of everyday life territorialized on the urban field, thinking of it as a field of conflicting forces which, sometimes, lead to impasses and falseconsensuses. Sete de Setembro Square, in Belo Horizonte, is the object of analysis, as also is its process of approval and construction initiated in 1989, within a National Contest of Architecture whose object of intervention was the central area of Belo Horizonte, the BH Centro until its remodeling, in 2003. Understanding the space of the square and itsproduction, not as a specific case but as a spatiality generated from the history of the city in which it exists, this work attempts to construct a critical analysis of the way by which the architects acted and redesigned such a space, from what institutional place did they project it and what kind of urbanity was generated from the concept within the project and itsmaterialization, pointing out which purposes such remodeling was attending to, as well as the new possibilities of professional exercise and latent propositions within such a spatial reality. This work is structured, in a first moment, within an analysis of the state of the art of the architect and urbanist professions and their relation with formalizing procedures from the 18th. Century until now, attempting to establish connections with the State, the space it produces and reproduces, and the nature of these relations produced within everyday life such as lived by the population. In a second moment, it establishes and discusses a new instrument to understand lived social space and its territorialized relations, as well as its production by proposing the following concepts: (F)ormalizations, (REF)ormalizations and (INF)ormalizations. Applying these concepts to the case of the Sete de Setembro Square within a historical contextualization of the city of Belo Horizonte, an attempt is made tounderstand the nature of the urban and of its production within a time-space scale. And finally, in the last chapter, looking at the generation and appropriation of the space by its users as well as at its constant shocks with other territorialized instances, an attempt is madeto propose new ways for the architect to act upon the urban field, as well to produce a knowledge of a proposing nature about the city and its spaces.